2002
DOI: 10.1034/j.1600-0463.2002.1101202.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining the glycophenotype of squamous epithelia using plant and mammalian lectins. Differentiation‐dependent expression of α2,6‐ and α2,3‐linked N‐acetylneuraminic acid in squamous epithelia and carcinomas, and its differential effect on binding of the endogenous lectins galectins‐1 and ‐3

Abstract: A thorough characterization of the properties of squamous epithelial cells is necessary in order to improve our understanding of the functional aspects of normal development and malignant aberrations. Up to now, studies have focused almost exclusively on monitoring distinct protein markers. With our growing awareness of the coding function of glycan chains of cellular glycoconjugates and their interaction with receptors (lectins) in situ, defining the glycophenotype of these cells has become an important issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The idea that ␣2-6 sialylation serves as an "on-off switch" for galectin binding and function is supported by studies of both synthetic oligosaccharides (20,44) and cell surface glycans (21,22,30,(45)(46)(47). ST6Gal-I selectively modifies N-glycans on CD45 to negatively regulate gal-1-induced T cell death (21).…”
Section: Discussionmentioning
confidence: 88%
“…The idea that ␣2-6 sialylation serves as an "on-off switch" for galectin binding and function is supported by studies of both synthetic oligosaccharides (20,44) and cell surface glycans (21,22,30,(45)(46)(47). ST6Gal-I selectively modifies N-glycans on CD45 to negatively regulate gal-1-induced T cell death (21).…”
Section: Discussionmentioning
confidence: 88%
“…Galectin-3 is expressed by epithelia lining the body surfaces that are exposed to Candida colonization, such as oral mucosa, corneal, and conjunctival epithelia, and intestinal epithelia (62)(63)(64)(65), that constitute the first line of host defense against Candida invasion. Although relatively high concentrations of soluble galectin-3 (20 M) were required to trigger Candida death in vitro, abundant galectin-3 has been detected in the local milieu surrounding inflammatory cells in human tissues (58), and galectin binding to extracellular matrix proteins has been shown to concentrate galectin (59).…”
Section: Discussionmentioning
confidence: 99%
“…Holikova et al (35) have shown that removal of ␣(2, 6) and ␣(2, 3)sialic acid increases Galectin-3 binding. Porcine and humans differ in the structure of their sialic acid residues.…”
Section: Discussionmentioning
confidence: 99%